Job Creation, Job Destruction and Plant Turnover in Norwegian Manufacturing - Tor Jakob Klette; Astrid Mathiassen (Statistics Norway, Research Department, 1995)
The labour market in Norway, as in other Scandinavian countries, is often claimed to be overregulated and incapable of adjustment to changes in job opportunities. The results presented in this paper suggest to the contrary that in terms of job creation and job reallocation between plants, the manufacturing sector in Norway is surprisingly flexible, and similar to the manufacturing sector in other OECD countries such as the U.S. We show that 8.4 percent of the manufacturing jobs are eliminated annually, while new jobs constitute 7.1 percent of manufacturing employment, in an average year. Even in a serious recession year, a considerable number of new jobs are created. The paper also examines job creation in small versus large plants (and firms), as well as young versus old plants. The results provide support to selection models a la Jovanovic (1982), while vintage-capital models seem to be largely irrelevant as models of plant heterogeneity.
Keywords: E32; J23; J63; 330; Job creation; job destruction; entry and exit.